O fenômeno da modalização como índice de argumentatividade no manual do professor de livros didáticos de língua portuguesa - França, Maria da Guia Santos de (2020)
This paper investigates the semantic-argumentative and pragmatic phenomenon of modalization in the manual genre of the Portuguese language teacher. In general, this research aims to describe and analyze the linguistic discursive functioning of the modalizers in the teacher's manual genre. Here, we specifically search for to identify the most frequent types of modalization in the manual, ascertain the effects of meanings generated by the use of these modalizers in the text and, finally, to verify which modalizers constitute a linguisticdiscursive characteristic of the teacher's manual genre. For that, the occurrence and the effects of the senses of the modalizers were analyzed in three 9th grade manuals, from the four most adopted collections, according to SIMADE data, by João Pessoa's municipal school system, in the state of Paraíba. Therefore, the methodological character of this research is of a qualitative, descriptive and interpretative nature, based on the investigations about the phenomenon of discursive modalization, presented by Cervoni (1989), Castilho e Castilho (2002), Koch (2009), Nascimento e Silva (2012). In addition, the concept of discursive genres postulated by Bakhtin (2010) was adopted, since the teacher's manual is considered as a discursive genre. The theoretical propositions of Andrade (2014) were also used, with regard to the Teacher's Manual. From the investigations carried out, it was possible to verify that the modalization consists of an argumentative phenomenon quite frequent in the manual genre of the teacher and that the deontic modalization and the evaluative modalization constitute the linguistic style of the genre. This is because these were the most frequent types of modalization in the corpus and because they play an important role with regard to the functionality of the genre, since they print guidance/instruction and an avaliation, respectively,by the speaker on the content of the said, thus guiding the interlocutor.